Hubungan Usia, Frekuensi ANC, dan Kepatuhan Konsumsi TTD dengan Kejadian Anemia Pada Ibu Hamil di Wilayah Kerja Puskesmas Turi, Kabupaten Lamongan - Aulia Maulidatuz Zahra (Lembaga Pengembangan Kinerja Dosen, 2025)
Anemia during pregnancy remains a widespread public health issue, especially due to iron deficiency. The purpose of this study was to explore the relationship between maternal age, number of antenatal care (ANC) visits, and compliance with iron supplement intake with the incidence of anemia among pregnant women at Turi Health Center in Lamongan Regency. This research employed a cross-sectional approach involving 55 pregnant women who were chosen using a multistage random sampling technique. Information was collected through interviews and hemoglobin level measurements conducted using a digital hemoglobin meterThe results indicated that 69.1% of the participants belonged to the non-risk age category, 34.5% exhibited moderate adherence to iron tablet intake, and 60% were found to be anemic. Statistical analysis revealed a significant correlation between maternal age (p = 0.004), number of ANC visits (p = 0.014), and compliance with iron supplement tablets (p = 0.000) with the level of anemia. This indicates the presence of a statistically significant association between maternal age, frequency of ANC visits, and level of compliance with iron supplement tablet consumption related to the incidence of anemia in pregnant women. Therefore, pregnant women are advised to have frequent ANC and consume iron supplement regularly to prevent anemia.